De Bonte Wei - Thijsse, Jac. P. (Jacobus Pieter), 1865-1945; Oort, Jan van, 1867-1938; Voerman, Jan, 1890-1976 (Salt Lake City, UT : Project Gutenberg, 2020)
"De Bonte Wei" by Jac. P. Thijsse is a natural history book written in the early 20th century. The work explores the beauty of the Dutch countryside, focusing on the flora and fauna found in meadows and fields, and aims to foster an appreciation for nature among readers of all ages. The opening of the work introduces readers to the author's childhood experiences in nature, highlighting a sense of wonder and curiosity about the plants and animals he encounters. From a young age, the author recounts his adventures exploring the outdoors, filled with encounters ranging from vibrant flowers to various insects and birds. He reflects on his fascination with a specific bird, the "spriet" or crake, and the joy of discovering its call while wandering through the summer meadows, emphasizing a deep connection to the natural world and hinting at the rich narrative and knowledge to come in the subsequent chapters. (This is an automatically generated summary.)
Release date is 2020-02-11
Produced by Jeroen Hellingman and the Online Distributed Proofreading Team at http://www.pgdp.net/ for Project Gutenberg.
Keywords: Natural history -- Netherlands -- Juvenile literature; Advertising cards -- Netherlands; Koninklijke Verkade (Firm) -- Collectibles